(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Palm Oil Mill Effluent (POME) contains a high number of organic materials that cause deleterious effects on the aquatic ecosystem when discharged into water bodies without proper pretreatment. The quality of POME final discharge is usually determined based on chemical monitoring methods such as Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD). In this study, biological monitoring methods were used to evaluate the toxicity effects of POME final discharge and to characterize the physical and chemical nature of toxicants present in the effluent through acute Whole Effluent Toxicity (WET) using Daphnia magna. The Toxicity Unit (TU) and median lethal concentration (LC50) of POME final discharge from the WET test were 11.09 and 9.02% (v/v), respectively. It is recommended that this method be improved to explore more effects of POME final discharge on the aquatic ecosystem.